1979
DOI: 10.1073/pnas.76.12.6120
|View full text |Cite
|
Sign up to set email alerts
|

Action of cathepsin D on human beta-lipotropin: a possible source of human "beta-melanotropin".

Abstract: Highly purified calf brain cathepsin D (EC 3.4.23.5) selectively splits the LeuO-Phe78 and Ala3-Ala37 peptide bonds of human P-lipotropin. It is suggested that the formation of human "jB-melanotropin" from y-lipotropin, and that of -y-endorphin from f.endorphin, is due to the action of cathepsin D during isolation procedures.Since the discovery of 3-lipotropin (3-LPH) and its isolation from ovine pituitaries (1), our knowledge of the chemistry of lipotropins has steadily grown. The complete amino acid seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1983
1983
1986
1986

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…4). The system used could separate hA3MSH- (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) and h/3MSH (Fig. 4A) peak was also detected with a shorter retention time (15 min) corresponding to an oxidized form of h,3MSH-(5-22).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4). The system used could separate hA3MSH- (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) and h/3MSH (Fig. 4A) peak was also detected with a shorter retention time (15 min) corresponding to an oxidized form of h,3MSH-(5-22).…”
Section: Resultsmentioning
confidence: 99%
“…The hypothalami and the nonpituitary tumors all contained hyLPH and a smaller molecular weight material that was only detected in the COOH-terminal hyLPH radioimmunoassay; its elution volume (Ve/V, 0.75) was identical to that of hJ3MSH-(5-22) but different from that of h.BMSH (Ve/V, 0.60); on reversed-phase HPLC, it coeluted with synthetic h.BMSH-(5-22) with a retention time different from that of hBMSH. It is concluded that hIBMSH- (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) that corresponds to the 18-amino acid peptide hfBLPH-(39-56), flanked by two pairs of basic amino acids within the h(3LPH molecule, is a normal maturation product of proopiomelanocortin in human nonpituitary tissues.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…During longer incubation of porcine/~-lipotropin the Ala3Z-Glu 33 peptide bond was cleaved as well by the enzyme preparation. The secondary cleavage site in human//-lipotropin was the Ala34-Ala 35 bond (Bar,it et al, 1979) (Fig. 2).…”
Section: Cathepsin Dmentioning
confidence: 99%
“…The enzyme displayed activity in the pH range 3.0-7.0 and was completely inhibited by 10 -6 M pepstatin. Cathepsin D purified from other tissues, such as human pituitaries (Benuck et al, 1978a;Bar,it et al, 1979) and bovine spleen, obtained as a commercial preparation (Burbach et al, 1980b), cleaved the Leu-Phe bond offl-endorphin or fl-LPH similarly (see also section 3.1.2. ).…”
Section: Purified Enzymes From Brain Tissuementioning
confidence: 99%